1976
DOI: 10.1055/s-0028-1093658
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration that Cyclic Adenosine 3',5'-Monophosphate Mediates the Lipolytic Action of Parathyroid Hormone

Abstract: Studies were carried out with rat epididymal fat pads first to compare the effects of the synthetic N-terminal 1-34 peptide of bovine parathyroid hormone and of the native hormone to determine whether this portion of the molecule is responsible for the lipolytic action of the hormone and second to determine whether this biologic action of parathyroid hormone is mediated by cyclic adenosine 3',5'-monophosphate. The N-terminal polypeptide was as effective as the native hormone in stimulating lipolysis in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Although very little is known about PTH signaling in adipose tissue, already more than 40 years ago it was reported that PTH induces lipolysis in rat and human fat explants with increased production of cAMP 20, 21. More recently, it was discovered that PTH promotes adipocyte lipolysis through cAMP-dependent activation of the PKA pathway, a downstream signal of the PTH receptor 13.…”
Section: Discussionmentioning
confidence: 99%
“…Although very little is known about PTH signaling in adipose tissue, already more than 40 years ago it was reported that PTH induces lipolysis in rat and human fat explants with increased production of cAMP 20, 21. More recently, it was discovered that PTH promotes adipocyte lipolysis through cAMP-dependent activation of the PKA pathway, a downstream signal of the PTH receptor 13.…”
Section: Discussionmentioning
confidence: 99%
“…LCR altered the expression of five genes encoding lipolysis-related proteins ( Table 4). β3-Adrenergic signals (1,2,42), parathyroid hormone (43), and growth hormone (44) promote lipolytic activities through their receptors. The receptors, β3-adrenergic receptor (b3ADr) and parathyroid hormone receptor (PTHr), were up-regulated by LCR, whereas low molecular weight growth hormone receptor/binding protein was down-regulated.…”
Section: Lcr Increases Expression Of Genes Associated With Lipid Metamentioning
confidence: 99%